Does crossing legs affect the measurement of blood pressure? [Abstract in English] - Koehler, Nelson Rudi (2011)
Aims: To compare oscillations in blood pressure with and without crossing legs. Methods: Eight serial measurements of blood pressure with intervals of one minute were made in each of 80 consecutive patients, in the sitting position. In the first half of the patients (Group 1, 40 patients), the four last measurements were taken after the patient crossed the legs at knee level. In the second half of the sample (Group 2, 40 patients), all the eight readings were done without crossing legs. Results: Systolic Blood Pressure in Group 1 oscillated from 132.4±20.9 mmHg pre-crossing to 137.3±24 mmHg post-crossing, and in Group 2, it changed from 132.1±16.2 mmHg in the first four measurements to 130.5±16,4 mmHg in the last four measurements. The variation in Group 1 was 4.9 and in Group 2 was -1.59 (range 6.5), and this difference was significant (p=0.001). Diastolic Blood Pressure in Group 1 varied from 80.9±4 mmHg pre-crossing to 82.3±14 mmHg post-crossing, and in Group 2, it varied from 79±11 mmHg to 80.1±11mmHg between the first four and last four measurements. The variation in Group 1 was 1.48 and in Group 2 was 0.79 (range 0.69), and this difference was not significant (p=0.59). Conclusions: There was a statistically significant but very modest increase in Systolic Blood Pressure from pre-crossing to post-crossing legs. There was no significant change between Diastolic Blood Pressure pre and post-crossing legs. In clinical practice, variation in blood pressure measurement with and without crossing legs has probably no clinical relevance, because of its little magnitude, similar to variation that occur at random.